Application of Pegadaian Digital Service Application in Pawn Transactions at PT. Pegadaian (PERSERO) UPC Katamso Medan - Nurul Azmi, Syahfrilla Al risa; Dharma, Budi (AMK : Abdi Masyarakat UIKA, 2023)
PT. Pegadaian (Persero) is a non-bank financial institution which is legally permitted to carry out credit financing on the basis of pawn law. PT. Pegadaian is currently carrying out transformation in the digital world by creating a web-based application called "Pegadaian Digital Service (PDS)". Pegadaian Digital Service (PDS) is a web-based pawnshop service to facilitate customer service in transactions. This research uses a qualitative approach with descriptive methods. The purpose of this research is to determine the use of the Pegadaian Digital Service (PDS) application to facilitate customer transaction services. The results of this research show that the use of the digital Pegadaian application makes customer service easier in transactions. However, it is still not running effectively in terms of facilities so it must be further improved which will have an impact on the quality of service.